1994
DOI: 10.1002/ana.410360508
|View full text |Cite
|
Sign up to set email alerts
|

Myelin basic protein peptide specificity and T‐cell receptor gene usage of HPRT mutant T‐cell clones in patients with multiple sclerosis

Abstract: Characterization of T cells responding to autoantigens is central to understanding autoimmune disease. We have used somatic mutation at the hypoxanthine guanine phosphoribosyltransferase (HPRT) gene as an index of T-cell amplification in vivo. With this strategy we previously showed that myelin basic protein-reactive T cells can be isolated only from the HPRT mutant T-cell population cultured from the peripheral blood of multiple sclerosis patients and not from normal individuals. In this study, 165 HPRT mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…MS is also characterized by increased oxidative stress (in PBMC and brain), which can cause DNA damage and somatic mutations 5456 . Further, T-lymphocytes isolated from MS patients that contain somatic mutations have been shown to react to myelin peptides 57 . Specifically, T-cell clones mutant for the hypoxanthine guanine phosphoribosyltransferase (HPRT) gene were found only in MS patients and not in HCs 57, 58 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MS is also characterized by increased oxidative stress (in PBMC and brain), which can cause DNA damage and somatic mutations 5456 . Further, T-lymphocytes isolated from MS patients that contain somatic mutations have been shown to react to myelin peptides 57 . Specifically, T-cell clones mutant for the hypoxanthine guanine phosphoribosyltransferase (HPRT) gene were found only in MS patients and not in HCs 57, 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, T-lymphocytes isolated from MS patients that contain somatic mutations have been shown to react to myelin peptides 57 . Specifically, T-cell clones mutant for the hypoxanthine guanine phosphoribosyltransferase (HPRT) gene were found only in MS patients and not in HCs 57, 58 . The MS patients studied had ‘chronic progressive MS’, clinically similar to the PPMS patients in this study 57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…enriched within the hprt mutant population of MS patients compared to the wild-type population (42,57). It has also recently been reported that hprt mutant cells from MS patients recognize myelin proteolipid protein peptides (58).…”
Section: T Cell Receptor Usage In Iddmmentioning
confidence: 94%
“…In diseases characterized by B-cell responses, these functions appear to be selectively reduced by cyclophosphamide therapy [28]. CD4 T cells are selectively depleted in MS patients treated with cyclophosphamide plus corticotropin [29] and evidence suggests that CD4+ cells are proliferating in MS patients based on studies of HPRT gene mutations [30,311. Taken together, these results suggest that cyclophosphamide may be inducing immune deviation by preferentially depleting T h l cells in MS, which then results in a skewed Th2 response and associated eosinophilia.…”
Section: Ifn--y Secretion In Treated Patientsmentioning
confidence: 99%